Scandals, morality wars, and the field of reproductive surrogacy in Ukraine - Alya Guseva (economic sociology_the european electronic newsletter, 2020)
Surrogacy - contracted gestation and birthing of babies for other people - is a multibillion-dollar global industry. Because it commodifies a practice that belongs to an intimate, "sacred" sphere of the family, and mixes babies and money, it offers a natural window into a theoretical problem of great interest to economic sociologists: the role of morality and moral framings in shaping and sustaining economic exchange.
Keywords: 300